UMUR DAN PARITAS IBU TERHADAP KEJADIAN KANKER SERVIKS - Arimina Hartati Pontoh (Jurnal Kebidanan Akademi Kebidanan Griya Husada Surabaya, 2018)
Patients with cervical cancer in Indonesia in 2014 turned out to be very large in number. According to the Surabaya City Health Office the incidence of cervical cancer in Surabaya in 2016 was 20%. Based on secondary data at Brawijaya Hospital Surabaya, cervical cancer has increased by 25.1% in 2016. So this problem is deemed necessary to do research that aims to determine whether there is a picture between maternal age and parity on the incidence of cervical cancer in Brawijaya Hospital Surabaya. Method: This study included a descriptive study using the Non Probability Sampling technique with saturated samples. Pap smear population of 137 people and a sample of 137 people. Secondary data collection from medical records of pap smear examination. The results of the study were made frequency tables, cross tabulations and analyzed. Results: The results showed that the majority of pregnant women suffering from cervical cancer were> 35 years old mother of 21 people (62.19%) while the majority of paremultipara parity was 22 people (34.37%) Discussion: From the results of the study it can be concluded that description of age and maternal parity of pap smears with the occurrence of cervical cancer. Therefore, to prevent the occurrence of cervical cancer, midwives should carry out counseling on reproductive health and make early detection of cervical cancer.